Global Diversification and Distribution of Coronaviruses With Furin Cleavage Sites - Liu, Xiaotong; Wu, Qunfu; Zhang, Zhigang (Frontiers in Microbiology, 2021)
Knowledge about coronaviruses (CoVs) with furin cleavage sites is extremely limited, although these sites mediate the hydrolysis of glycoproteins in plasma membranes required for MERS-CoV or SARS-CoV-2 to enter cells and infect humans. Thus, we have examined the global epidemiology and evolutionary history of SARS-CoV-2 and 248 other CoVs with 86 diversified furin cleavage sites that have been detected in 24 animal hosts in 28 countries since 1954. Besides MERS-CoV and SARS-CoV-2, two of five other CoVs known to infect humans (HCoV-OC43 and HCoV-HKU1) also have furin cleavage sites. In addition, human enteric coronavirus (HECV-4408) has a furin cleavage site and has been detected in humans (first in Germany in 1988), probably via spillover events from bovine sources. In conclusion, the presence of furin cleavage sites might explain the polytropic nature of SARS-CoV-2- and SARS-CoV-2-like CoVs, which would be helpful for ending the COVID-19 pandemic and preventing outbreaks of novel CoVs.